Strategic human resource management practices and performance of sugar manufacturing firms in Western Kenya - Florah, Oluoch Mercy; Nyagol, Michael O.; Rabah, Susan A. (IJRSS, 2013)
The study used a cross-section descriptive survey design in which 8 human resource managers in 8 sugar manufacturing firms in Western Kenya were investigated. Strategic human resource management practices were based on the key functions namely: recruitment and selection, training and development, training effectiveness and evaluation, performance-based compensation, flexible benefits, employee relations practices, consultative performance appraisal and human resource planning. The study examined the performance of the firms based on performance indicators such as quality of products, services or programmes and development of new products, services or programmes, efficiency in operations, profitability and sales growth, using Pearson product moment correlation technique. The results revealed positive correlations ranging between 0.4 and 0.7 meaning that with improvement in Strategic Human Resource Management Practices, Firm Performance also increased. Thus the findings support the universalistic perspective